2016
DOI: 10.21070/kanal.v1i1.326
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Promosi Sekolah Terhadap Keputusan Siswa Dalam Pemilihan SMK Sepuluh Nopember Sidoarjo

Abstract: ABSTRAKKeputusan memilih siswa untuk menuntut ilmu di SMK Sepuluh Nopember salah satunya disebabkan adanya promosi yang dilakukan oleh pihak sekolah dalam menarik minat calon-calon siswa. Penelitian ini dilakukan untuk mengetahui pengaruh promosi terhadap keputusan siswa dalam memilih sekolah di SMK Sepuluh Nopember. Variabel dalam penelitian ini adalah promosi sekolah sebagai variabel independen dan keputusan memilih sebagai variabel dependen. Subjek penelitian ini adalah siswa SMK Sepuluh Nopember sebanyak 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…Fadjrin and Muhsin's (2017) research showed that there was a positive and significant influence on the partial promotion of school on the interest of students choosing majors. The results of the study by Gusdiandika and Sinduwiatmo (2012) also explained that there was an influence of school promotion activities on the decision of students to choose schools in SMK.…”
Section: The Effect Of School Promotion On the Decision To Choose Expertise Competencies In Class Xmentioning
confidence: 90%
See 1 more Smart Citation
“…Fadjrin and Muhsin's (2017) research showed that there was a positive and significant influence on the partial promotion of school on the interest of students choosing majors. The results of the study by Gusdiandika and Sinduwiatmo (2012) also explained that there was an influence of school promotion activities on the decision of students to choose schools in SMK.…”
Section: The Effect Of School Promotion On the Decision To Choose Expertise Competencies In Class Xmentioning
confidence: 90%
“…for the selection of majors by Muhammadiyah Vocational School students in Bantul because of presentations that are easily recognized from SMKs who come to SMP / MTs. Gusdiandika & Sinduwiatmo (2012) explained that in direct marketing, given the ease, presentation, and question and answer. Based on the results of interviews with students told that the performances of vocational competencies held by vocational schools were engaging, easy to understand, and transparent.…”
Section: The Effect Of School Promotion On the Decision To Choose Expertise Competencies In Class Xmentioning
confidence: 99%
“…Hasil penelitian ini memiliki keterkaitan dengan penelitian yang dilakukan oleh (Gusdiandika & Sinduwiatmo, 2012) dengan hasil penelitianya menyatakan bahwa ada pengaruh promosi terhadap keputusan siswa dalam memilih SMK Sepuluh Nopember Sidoarjo. Selain itu pada penelitian Jarot Tri (Santoso, 2014) dalam hasil penelitianya menyatakan bahwa Berdasar hasil analisis data bahwa promosi SMK, lokasi SMK, latar belakang sosial ekonomi, referensi orang terdekat dengan siswa, persepsi siswa tentang SMK, motivasi siswa, jurusan yang ditawarkan SMK secara bersama sama mempunyai pengaruh terhadap minat siswa SMP dalam memilih SMK.…”
Section: Hasil Dan Pembahasanunclassified
“…Promotion is an activity to display the advantages of products or serv ices owned by the general public, aiming to persuade customers to buy a product or service (Kotler, 2012;Kotler & Keller, 2012). The promotions carried out by IKHAC include visiting schools, installing banners, brochures and using social media research by (Gusdiandika & Sinduwiatmo, 2016), promotions consisting of advertising and direct marketing have an influence on school selection decisions by students of SMK 10 November Sidoarjo.…”
Section: Introductionmentioning
confidence: 99%